Water Quality Assessment of the Inanam River in Kota Kinabalu, Sabah, Malaysia - Cleophas, Fera; Zahari, Nur Zaida; Adnan, Farrah Anis Fazliatul; Budin, Kamsia; Saleh, Hardianshah; Musta, Baba (Journal of Environmental Microbiology and Toxicology, 2025)
This study provides a comprehensive assessment of the water quality of the Inanam River, Kota Kinabalu, Sabah, Malaysia, across four sampling stations from upstream to downstream. Both in-situ and ex-situ analyses were performed to evaluate physicochemical and biological parameters, including BOD, COD, ammoniacal nitrogen (AN), TSS, DO, pH, temperature, TDS, salinity, electrical conductivity (EC), fecal coliform, and total coliform. The Water Quality Index (WQI) was determined following Malaysia’s National Water Quality Standards (NWQS). Findings reveal that the Inanam River falls into Class II and Class III categories, with DO, COD, and AN levels in several locations meeting or exceeding Class III thresholds, particularly in downstream segments. Urban stretches exhibited the most significant water quality deterioration, highlighting the urgent need for targeted pollution control and management interventions.